2012
DOI: 10.1111/j.1438-8677.2012.00607.x
|View full text |Cite
|
Sign up to set email alerts
|

Methylglyoxal inhibits seed germination and root elongation and up‐regulates transcription of stress‐responsive genes in ABA‐dependent pathway in Arabidopsis

Abstract: Methylglyoxal (MG) is a highly reactive metabolite derived from glycolysis. In this study, we examined the effect of MG on seed germination, root elongation, chlorosis and stress-responsive gene expression in Arabidopsis using an abscisic acid (ABA)-deficient mutant, aba2-2. In the wild type, 0.1 mm MG did not affect germination but delayed root elongation, whereas 1.0 mm MG inhibited germination and root elongation and induced chlorosis. MG increased transcription levels of RD29B and RAB18 in a dose-dependent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
37
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(40 citation statements)
references
References 31 publications
(33 reference statements)
3
37
0
Order By: Relevance
“…MG has a positive effect on differentiation and shoot morphogenesis of tobacco callus ( Nicotiana tabacum L.) [73]. MG is also an inhibitor of seed germination and root elongation in plants [74]. MG is known to induce expression of stress-responsive transcription factors RD29B and RAB18 in a concentration-dependent manner through an ABA-dependent pathway [74].…”
Section: Functional Roles Of Glyoxalases In Plants: From the Past mentioning
confidence: 99%
See 1 more Smart Citation
“…MG has a positive effect on differentiation and shoot morphogenesis of tobacco callus ( Nicotiana tabacum L.) [73]. MG is also an inhibitor of seed germination and root elongation in plants [74]. MG is known to induce expression of stress-responsive transcription factors RD29B and RAB18 in a concentration-dependent manner through an ABA-dependent pathway [74].…”
Section: Functional Roles Of Glyoxalases In Plants: From the Past mentioning
confidence: 99%
“…MG is also an inhibitor of seed germination and root elongation in plants [74]. MG is known to induce expression of stress-responsive transcription factors RD29B and RAB18 in a concentration-dependent manner through an ABA-dependent pathway [74]. In many of these experiments with exogenous application of MG, the concentration of MG used (0.1–10 mM) is 25–2500-fold higher than the physiological levels found in plants, raising the possibility that the observed changes are likely the result of acute intoxication of plant tissues by exogenous MG. We also have to take into consideration that, during exogenous application of chemicals to plant tissues, it is typical to apply higher concentrations in order to observe a physiological effect.…”
Section: Functional Roles Of Glyoxalases In Plants: From the Past mentioning
confidence: 99%
“…MG at 1 mM concentration could increase cytosolic Ca 2+ oscillations in the guard cells that were suppressed by pretreatment with 1 mM SHAM. Collectively, this data indicated that MG-induced stomatal closure involves an extracellular oxidative burst, which diffuses into the intracellular space leading to intracellular ROS accumulation in guard cells, and this result in stomatal closure via Ca 2+ -dependent pathway (Hoque et al 2012c ). In addition, MG can also inhibit lightinduced stomatal opening in Arabidopsis by inhibiting K + infl ux into the guard cells, which most likely occurs via the modifi cation of C-terminal region of the inward-rectifying potassium channel (Hoque et al 2012d ).…”
Section: Methylglyoxal As a Signaling Molecule In Biological Systemsmentioning
confidence: 86%
“…The involvement of MG in inducing stomatal closure, ROS production, and cytosolic-free calcium concentration has been investigated in order to clarify its role in Arabidopsis guard cells (Hoque et al 2012c ). MG was found to reduce stomatal apertures in a dose-dependent manner with the process being reversible at only low MG concentration (1 mM).…”
Section: Methylglyoxal As a Signaling Molecule In Biological Systemsmentioning
confidence: 99%
“…In terms of morphological changes, we have shown that plants with high endogenous MG levels under stress conditions exhibit growth and development defects (Singla-Pareek et al, 2003, 2008Kaur et al, 2017;Gupta et al, 2018). Furthermore, MG at 1 mM inhibits seed germination and root elongation and induces chlorosis in Arabidopsis (Hoque et al, 2012). In view of MGmediated glycation, researchers have identified 'dicarbonyl proteomes' in animals and plants, comprising proteins susceptible to MG-mediated modification.…”
Section: Different Shades Of Methylglyoxal: Cytotoxin or A Signal mentioning
confidence: 99%